2012
DOI: 10.1371/journal.pntd.0001702
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Clinical and Histological Diagnosis of Leprosy and Leprosy Reactions in the INFIR Cohort of Indian Patients with Multibacillary Leprosy

Abstract: BackgroundThe ILEP Nerve Function Impairment in Reaction (INFIR) is a cohort study designed to identify predictors of reactions and nerve function impairment in leprosy. The aim was to study correlations between clinical and histological diagnosis of reactions.Methodology/Principal FindingsThree hundred and three newly diagnosed patients with World Health Organization multibacillary (MB) leprosy from two centres in India were enrolled in the study. Skin biopsies taken at enrolment were assessed using a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 13 publications
2
42
0
2
Order By: Relevance
“…The INFIR study pointed out the important role that pathologists in leprosy centers play supporting and helping clinicians with difficult cases. 10 This study indicated that slit-skin smear results, serological tests, and the WHO classification criterion were consistent with the R&J classification. We acknowledge that all classification approaches investigated herein had limitations.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The INFIR study pointed out the important role that pathologists in leprosy centers play supporting and helping clinicians with difficult cases. 10 This study indicated that slit-skin smear results, serological tests, and the WHO classification criterion were consistent with the R&J classification. We acknowledge that all classification approaches investigated herein had limitations.…”
Section: Discussionsupporting
confidence: 73%
“…Indeterminate leprosy patients were excluded. patients with high BI have a higher risk of developing reactions, [10][11][12] but besides the high BI other unknown factors play a role in the susceptibility to leprosy reactions. Previous results of U-MDT/CT-BR trial showed that there is no statistical difference between U-MDT or regular-MDT (R-MDT) treatment regimen regarding frequency of reactions among MB patients, even when BI was stratified as BI or 3.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterogeneity of the RR samples may relate to differences in the severity and/or duration of the reactional state or intrinsic host ability to respond, as was also observed for RR blood samples (17). It is noteworthy that the histologic differentiation of T-lep and RR forms is often difficult (18,19). In contrast, the ENL samples formed a separate group that was equally dissimilar to both the L-lep and T-lep/RR clusters.…”
Section: Resultsmentioning
confidence: 87%
“…Special stains play a supportive role in infectious granulomas. [7,8] The aim of this study is to determine the etiology and study the morphology of all granulomatous skin lesions evaluated histopathologically and to determine relative frequencies of different infectious granulomatous conditions.…”
Section: Introductionmentioning
confidence: 99%